Poly(3-octylthiophene)/stearic acid langmuir and langmuir-blodgett films: preparation and characterization - Silva, Edilene Assuncao da [UNESP]; Rodrigues de Oliveira, Vinicius Jesse [UNESP]; Braunger, Maria Luisa [UNESP]; Leopoldo Constantino, Carlos Jose [UNESP]; Olivati, Clarissa de Almeida [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
A study is reported on Langmuir and Langmuir-Blodgett (LB) films obtained by adding different percentages of stearic acid (SA) to poly(3-octylhiophene) (P3OT). Surface pressure-mean molecular area (pi-A) isotherms, ultraviolet-visible (UV-Vis) absorption spectrum, atomic force microscope (AFM) and dc electrical measurements have been used for characterization. From p-A isotherms, the area per monomer for condensed films (of SA) increased according to P3OT amount. Good transfer ratios were obtained for LB deposition from P3OT/SA films with higher percentage of SA. LB films revealed linear growth as monitored by UV-Vis absorption spectra. Electrical characterization showed higher conductivity for LB film with 54 wt.% of SA. AFM images of the same film revealed high roughness and presence of large size agglomerates. Finally, interdigitated electrodes (IDE) coated with P3OT/SA LB films showed to be sensitive to the presence of volatile organic compounds.
Keywords: Langmuir; Langmuir-Blodgett; Polythiophenes; Electrical characterization; Sensors